Recent developments in choledochoscopy: technical and clinical advances - Xu MM; Kahaleh M (Clinical and Experimental Gastroenterology, 2016)
Ming-Ming Xu, Michel Kahaleh Division of Gastroenterology and Hepatology, Weill Cornell Medical College, Cornell University, New York, NY, USA Abstract: Peroral cholangioscopy has become an important tool in the diagnosis and treatment of a variety of biliary diseases, ranging from indeterminate biliary strictures to bile duct stones. Although the first cholangioscopy was performed in the 1970s, recent technological advances have provided us with cholangioscopes that yield high-resolution images, possess single-operator capability, and have ultrathin design to allow easier maneuverability and detailed imaging of the biliary tract. We review here the currently available devices for peroral cholangioscopy, their clinical applications, limitations, and complications. Keywords: peroral cholangioscopy, videocholangioscopy, single-operator cholangioscopy, SOC, electrohydraulic lithotripsy